Effects non-digested and anaerobically digested farmyard manures on wheat crop cultivated in desert soil - Abubaker, Jamal Abdallah Ahmed; Elnesairy, Nazar; Ahmad, Sanussi (Journal of Aridland Agriculture, 2017)
Digesting animal manure anaerobically before applying it as fertilizer may be affected crop production differently compared to non-digested particularly in desert soils. A pot experiment was carried out to evaluate three non-digested (NDM) and digested (DM) farmyard manures (cattle, poultry, and sheep) and their combinations with urea on the wheat crop cultivated in desert soil. Fertilizers were applied at rates corresponding to 50, 150 and 250 kg Tot N ha-1. During the growing period, seed germination percentage (SGP), plant height, plant tillering percentage (PTP) and deficiency symptoms were assessed. Furthermore, total biomass yield and relative yields of ear, straw and root fractions were measured at harvest. Results showed that high application of DM reduced SGP significantly (p<0.05), especially at the combination with urea. PTP was higher in non-digested manure treatments of sheep and poultry than DM, and also higher in digested cattle manure treatments than NDM, while it was zero in all urea treatments and control. Deficiency symptoms were seen in the treatments of low application rate as well as in all urea treatments and control. Plant height and biomass yield generally increased in NDM and DM treatments compared with urea treatments and the control. Beneficial of DM was seen in cattle and poultry manure treatments where they significantly (p<0.05) yielded higher root, ears, and total biomass compared to NDM. However, non-digested sheep and poultry manure yielded higher straw biomass than DM. The combination of non-digested and digested manure with urea gave the maximum biomass yield, especially in combination with digested poultry manure.